Convergence ou divergence ? Analyse comparée du rôle des « résultats d'apprentissage » dans les curriculums de l'enseignement professionnel de base de neuf pays européens - Léna Krichewsky; Dietmar Frommberger (Les éditions de la Maison des sciences de l'Homme, 2013)
Under the combined action of European cooperation in vocational training, transformations of the labor market, and new governance practices, the European Union countries have undertaken substantial reforms of their systems of vocational education and training. A privileged instrument of these reforms is the curriculum, understood here as the normative framework (broadly defined) regulating the learning process. Based on a case study in nine European countries, the authors question the use of "learning outcomes" in the curriculum. At a time when the interactions between national systems are increasingly dense, they propose to explore the implications of this concept in terms of regulative and pedagogical approach, so as to better understand current developments and assess the extent of a possible convergence of national systems towards a single model.